Prolactinoma: A Massive Effect on Bone Mineral Density in a Young Patient - Scott Sperling; Harikrashna Bhatt (Case Reports in Endocrinology)
This case highlights a prolactinoma in a young male, and its impact on bone health. Osteoporosis has been noted to be an issue in postmenopausal women with prolactinomas. This case shows a similar impact on bone health in a young male resulting in low bone mineral density for age based on Z-score. This case report highlights the possible mechanisms for the bone loss in the setting of prolactinoma and the need for assessing bone health in such patients. Furthermore it highlights the need for a thorough evaluation in such patients.